Preparation, Characterisation and Reactions of Symmetrical and Unsymmetrical Tris(Pentafluorophenyl)Antimony(V) Amides (Global Journal of Science Frontier Research, 2014)
Abstract not found
Keywords: tris(pentafluorophenyl)antimony(v); symmetri -cal; unsymmetrical; metathesis; triethylamine